Trends in the diagnostic delay and pathway for amyotrophic lateral sclerosis patients across different countries - Falcão de Campos, Catarina; Gromicho, Marta; Uysal, Hilmi; Grosskreutz, Julian; Kuzma-Kozakiewicz, Magdalena; Oliveira Santos, Miguel; Pinto, Susana; Petri, Susanne; Swash, Michael; de Carvalho, Mamede (Frontiers in neurology, 2023)
Amyotrophic lateral sclerosis (ALS) is a rapidly progressive neurodegenerative disease with a median survival of 2-5 years. An early diagnosis is essential for providing ALS patients the finest management possible. Studies from different countries report a similar median diagnostic delay of around 12 months, which is still far from desirable. We analyzed the diagnostic pathway in different countries in order to identify the major challenges. We studied a cohort of 1,405 ALS patients from five different centers, in four different countries (Turkey, Germany, Poland, and Portugal), which collaborated in a common database. Demographic, disease and sociocultural factors were collected. Time from first symptom onset to first medical evaluation and to diagnosis, the specialist assessment and investigations requested were analyzed. Factors contributing to diagnostic delay were evaluated by multivariate linear regression. The median diagnostic delay from first symptom onset was 11 months and was similar between centers. Major differences were seen in the time from symptom onset to first medical evaluation. An earlier first medical evaluation was associated with a longer time to diagnosis, highlighting that ALS diagnosis is not straightforward in the early stages of the disease. The odds for ALS diagnosis were superior when evaluated by a neurologist and increased over time. Electromyography was decisive in establishing the diagnosis. We suggest that a specific diagnostic test for ALS-a specific biomarker-will be needed to achieve early diagnosis. Early referral to a neurologist and to electromyography is important for early ALS diagnosis.